2015
DOI: 10.17221/108/2014-agricecon
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the state of the Business Intelligence among small Czech farms

Abstract: Business Intelligence (BI) can assist in agricultural enterprises to strengthen their production potential and technical effi ciency due to its eff ective support to the managerial, analytical, planning, and decision-making activities of managers and specialists. However, the state of the BI in the Czech Republic is not still completely understood. In this context, this paper aims at the evaluation of the current state of the art of the BI among small Czech farms. Th e focus of the re search was put on the eva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 34 publications
0
11
0
2
Order By: Relevance
“…This fact impacts also on demonstration activities which are relatively on a high professional level. On the other side, farms with less than 500 ha and fewer than three employees have significantly worse information coverage [30][31][32].…”
Section: The Czech Agriculture and A Development Of Innovations In Thmentioning
confidence: 99%
“…This fact impacts also on demonstration activities which are relatively on a high professional level. On the other side, farms with less than 500 ha and fewer than three employees have significantly worse information coverage [30][31][32].…”
Section: The Czech Agriculture and A Development Of Innovations In Thmentioning
confidence: 99%
“…However, according to Tyrychtr et al (2015) agricultural holdings predominantly focus on technical performance (more than 50 % of all companies), only then on financial performance. At the same time, share of companies targeted at the efficient economic agriculture is increasing.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…The survey by Hamranová (2013) also showed that only 22% of the companies have implemented the business intelligence applications, which confirms the low penetration of the implementation of these tools. Business intelligence applications have a justified significance also in agricultural enterprises (Tyrychtr et al 2015). The current business intelligence applications are all about flexibility, interactivity, getting in the shortest possible time and in the easiest way the most accurate information from which a new fact can be deducted; just to get a certain added value out of it for the management or decision making.…”
Section: Level 3 (70% < X ≤ 100%) -Intensive Usementioning
confidence: 99%